Development and storage studies of high density macrocapsules containing Lactobacillus spp. strains as nutritional supplement in young calves = Desarrollo de macrocápsulas con cepas de Lactobacillus spp. en alta densidad como suplemento nutricional de terneros jóvenes y análisis de su viabilidad durante el almacenamiento - Astesana, Diego Martín; Zimmermann, Jorge Alberto; Frizzo, Laureano Sebastian; Zbrun, María Virginia; Blajman, Jesica E.; Berisvil, Ayelén Patricia; Romero Scharpen, Analía; Signorini, Marcelo; Rosmini, Marcelo Raúl; Soto, Lorena Paola (2018)
The aim of this study was to evaluate different production methodologies of probiotic macrocapsules with high bacterial densities destined to lactating calves. Three types of capsules containing Lactobacillus casei DSPV318T and Lactobacillus plantarum DSPV354T were prepared from an overnight culture in whey medium: (1) mixing the culture with calcium alginate and then, reincubating the capsules in whey (RC); (2) concentrating the biomass by centrifugation and mixing the pellet with calcium alginate (CC) at different concentrations with respect to the initial culture (5X and 12.5X); (3) CC with cryoprotectants: whey permeate (Per) and glycerol (Gly). Chitosan coating was evaluated. Capsules were freeze-dried and viability was assessed before freezing, after freeze-drying and every two weeks for 84 days of storage at room temperature, 4 °C and −20 °C. CC showed higher cell densities than RC. Storage temperature affected viability: greater viability at lower temperature. Moreover, the effect of temperature was influenced by other factors, such as capsule coating, culture neutralization and cryoprotectants. Coating improved viability at room temperature; however no effect was observed at 4 °C. Culture neutralization allowed greater survival during storage. Cryoprotectants improved viability during freezing, but they also generated a positive or negative effect depending on storage temperature. The best results were: at refrigeration Gly12.5X exhibited counts above 109 CFU/capsule until day 70 and Per12.5X until day 56 of storage and at −20 °C Gly12.5X showed counts above 109 CFU/capsule until the end of the study (84 days). A 109 CFU capsule is the daily dose per calf which would facilitate the administration of this probiotic inoculum to field animals.